Carriers of multiresistant bacteria of clinical importance in critical areas (ICU - INCU) from a Hospital at north of Peru - Aguilar Gamboa, Franklin Rómulo (2016)
Objective: To determine the frequency of multiresistant bacteria Carriers (BM) and its profile of resistance in critical areas (ICU-INCU) in a public hospital in northern Peru (HRL). Material and methods: A cross-sectional observational study was conducted during February to May 2015, in 48 patients and 32 healthcare staff. 4 anatomical regions for sampling were considered and supplemented instruments with antibiotics were used for primary isolation of BM. The resistance phenotype was confirmed by Jailer's test, Modified Hodge and susceptibility to cefoxitin. Results: The frequencies of BM in patients and healthcare staff were 79.1% and 3.1% respectively; also 89.5% of patients were already carriers at the time of admission mainly from Emergency Service, being anorectal region the principal source of isolates with 75.0%. It also was determined that production of extended spectrum beta-lactamase (ESBL) was the principal resistance phenotype with 77.65%, followed by the production of carbapenemases and methicillin resistance with 14.2% and 8.24% respectively. Conclusions: This study reveals the high frequency of multiresistant bacteria carriers in patients in critical areas of HRL and that most of these already were colonized in the anorectal region.